IN PARTICULAR OF UNIVERSITY STUDENTS THE MEDIATING ROLE OF CONSUMER BASED BRAND EQUITY IN THE EFFECT OF BRAND LOVE ON BRAND LOYALTY (Third Sector Social Economic Review, 2022)
Smart phone brands are trying to gain sustainable advantage in the global competitive environment for the appreciation of consumers. A satisfied consumer can use smart phone brand for a long time and can choose a new model of the same brand when he/she wants to renew it. Although the concept of brand love has attracted the attention of brand managers, there is not much information about the elements that make up brand love and behavioral consequences. When the loyalty of the consumer to the brand increases, the brand's value also increases, so brand loyalty and consumer-based brand equity are closely related. In this study, it is aimed to analyze the effect of brand love on brand loyalty in terms of smart phone use of university students, through the mediating role of consumer-based brand equity. In this research, survey data were obtained from 378 students selected from two private universities in TRNC with the convenient sampling method. Descriptive statistical analyzes were made with these data and the validity and reliability of the scales used in the study were tested. Correlation analysis was conducted to determine the relationship between variables. Research hypotheses were tested with the “process macro”. According to the findings obtained in the study; it has been determined that brand love has a significant and positive effect on brand loyalty and consumer-based brand equity has a full mediator role in this relationship. It is considered that the findings of the study will contribute to the literature on brand loyalty and will attract the attention of businesses operating in the smart phone industry.
Keywords: Consumer; Brand Loyalty; Brand Love; Consumer Based Brand Equity; Smart Phone Usage